Faktor-Faktor Yang Mempengaruhi Nilai Impor Pesawat Boeing Amerika Serikat 1990-2010 - Mustika, Satya Haridyantha; Suresmiathi, A.A. Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 7, Juli 2014 (pp.282-336), 2014)
The value of imports plane made by PT. Garuda Indonesia Airlines had made the country foreign exchange reserves to the deficit. On the other hand, the country has PT. Dirgantara Indonesia for development and production of the plane. Resources and expensive cost of research into the company to import plane. This research using secondary data and using analysis of multiple linear. The aim of this research, (1) if the demand, inflation, dollar rate of United States, reserves simultaneously and partial influence significantly towards the United States imported the plane by a Boeing company. Garuda Indonesia Airlines, (2) to know the most dominant variable effect on imports Boeing aircraft United States. The result that the number of requests, inflation dollar exchange rate and and reserves directly affect the import value the Boeing company Garuda Indonesia Airlines 1990-2010 period. Besides, the request and would not affect the partial on imports and dollar exchange reserves have negative and positive impact. The variables is the dominant foreign exchange reserves.
Keywords: imports , demand for services inflation dollar exchange rate , foreign exchange reserves